EFEKTIVITAS DAN EFIESIENSI PENERAPAN APLIKASI PENDAFTARAN ANTRIAN PASPOR ONLINE DI KANTOR IMIGRASI KELAS 1 TPI SAMARINDA - Harmitalia, Mita; Irawan, Bambang; Khaerani, Thalita Rifda (Journal of Policy & Bureaucracy Management, 2021)
Online Passport Queue Registration Application (OPQRA) is an innovation in the Document Application Service Travel of the Republic of Indonesia (Passport). By using qualitative descriptive methods, this study aims to determine and analyse the effectiveness and efficiency of the implementation of OPQRA at the Immigration Office Class 1 Immigration Checkpoint (IC) Samarinda and to describe thoroughly the differences between the application of offline queuing and online queuing using OPQRA, as well as the inhibiting factors in the implementation of OPQRA. The results showed that the implementation of OPQRA at the Immigration Office Class 1 Immigration Checkpoint Samarinda has been running effectively and efficiently, this can be proven by the absence of long queues, the quota of passport applicants at OPQRA provided is always available, there are no illegal levies or no practice brokering in passport services. OPQRA outreach has been held thorugh social media and print media. The existence of OPQRA really helps the community to be more effective in making passports as well as being more efficient because it saves time and costs compared to using an offline queue. Another finding is that there are inhibiting factors in the application of OPQRA in the form of network quality constraints, applications that sometimes have errors, websites that cannot be reached to register online, and OPQRA which can only be uploaded via mobile phones with an android system.